Student Perception on the Use of YouTube Videos as Learning Material for Speaking Activities: A Case Study of Teaching Speaking at Vocational Schools - Lailika, Salma Novia (RETAIN : Journal of Research in English Language Teaching, 2023)
The purpose of this study is to find out students' perceptions of using YouTube in vocational schools. Learning material to study and improve a skill is essential to delivering the lesson, especially for vocational students who can develop English language skills according to their expertise. YouTube is an effective learning material for improving students speaking skills. YouTube provides some video material that the students can study, observe, and imitate while learning, such as how to talk with good pronunciation, how to communicate in a particular situation, etcetera. The students will have more opportunities to learn about speaking orally during learning on YouTube, and there is a lot of learning material that can be referenced about speaking to communicate in a good way. In this study, the researcher examined SMK 1 and SMK Wijaya so that the researcher could find out the errors and strive experienced by the students during learning. It could be developed in education using YouTube by public and private schools. The researcher used a questionnaire to find the perspective of the students. The two proposition presented from this study is to know how vocational students perceive the use of YouTube as learning material for speaking class and whether the YouTube video as learning material is substantial for vocational school. There are many ways to improve students' speaking skills. While in this case, based on the study in that two schools, most students have good taste in using YouTube. Students' perspective while implementing YouTube videos as learning material is positive, and many students are highly interested in using YouTube. YouTube is one of the tools as learning material that can make students easier to understand the material. So, YouTube is an essential thing for vocational schools.